Glucocorticoid receptor-mediated delivery of nano gold–withaferin conjugates for reversal of epithelial-to-mesenchymal transition and tumor regression. (October 2016) - Agarwalla, Pritha; Mukherjee, Sudip; Sreedhar, Bojja; Banerjee, Rajkumar
Aim: To explore the potential of glucocorticoid receptor-targeted nano-gold formulation as antitumor drug sensitizing agent.Materials & methods: Simultaneous conjugation of gold nanoparticle with thiol-modified dexamethasone, a synthetic glucocorticoid and anticancer drug withaferin A afforded stable gold nanoparticle-modifed dexamethasone-withaferin A nanoconjugate.Results: This metallic nanoparticle formulation showed glucocorticoid receptor-dependent cancer cell selective cytotoxicity, inhibited growth of aggressive mouse melanoma tumor, reduced mice mortality, while reversing epithelial-to-mesenchymal transition in tumor cells. Same treatment also leads to near-complete downregulation of ABCG2 drug transporter in tumor-associated cells thus attributing it to its drug sensitizing ability.Conclusion: The presently synthesized nanoconjugate holds a great promise to sensitize cancer cells to chemotherapeutics and induce epithelial-to-mesenchymal transition reversal in tumor cells preventing metastasis.